1998
DOI: 10.1128/jcm.36.12.3549-3551.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Abbott LCx Assay for Detection of Neisseria gonorrhoeae in Endocervical Swab Specimens from Females

Abstract: The Abbott LCx Neisseria gonorrhoeae assay (Abbott Laboratories, Abbott Park, Ill.) uses a ligase chain reaction (LCR) amplification in the LCx probe system for detection of a specific nucleotide sequence in the Opa-encoding gene of N. gonorrhoeae. We evaluated the LCx assay in a comparison with conventional culture employing modified Thayer-Martin media for the detection of N. gonorrhoeae from female endocervical specimens obtained from patients attending a sexually transmitted disease clinic. Discordantly LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The published LCx studies calculated performance as if only one specimen type from each patient had been tested by the LCx. Compared to COBAS AMPLICOR performance calculated on a per-specimen basis, the LCx exhibited very similar sensitivities for female endocervical swabs (3,4,10), male urethral swabs (3,4), and male urine (3). In contrast, LCx sensitivity was approximately 20% higher for female urine (16,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published LCx studies calculated performance as if only one specimen type from each patient had been tested by the LCx. Compared to COBAS AMPLICOR performance calculated on a per-specimen basis, the LCx exhibited very similar sensitivities for female endocervical swabs (3,4,10), male urethral swabs (3,4), and male urine (3). In contrast, LCx sensitivity was approximately 20% higher for female urine (16,20).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of culturing is that it requires invasively collected endocervical or urethral swab specimens. Recent studies have shown that a nucleic acid amplification-based test can achieve high sensitivity and specificity for the detection of N. gonorrhoeae (4,8,10,12,16). This test can be performed on self-collected urine, vaginal, and vulval specimens (8,20; A. Stary and B. Hartman, Program Abstr.…”
mentioning
confidence: 99%
“…Nucleic acid amplification tests (NAATs), either in‐house or commercial assays, targeting N. gonorrhoeae have been shown to have varying degrees of specificity and sensitivity [6–11]. NAATs do not require viable bacteria, and can therefore circumvent the problems of specimen collection and transportation for this fragile organism, especially when specimens are collected in remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of new assays that have superior sensitivities compared with current test methods is challenging, as evidenced by the introduction of nucleic acid amplification tests for Neisseria gonorrhoeae and Chlamydia trachomatis [ 13 , 14 ]. The specificity of the PCR assay studied here was not in question as it was determined to be high in our validation studies with no cross-reactivity demonstrated with a wide variety of microorganisms that may be present in human respiratory specimens (data not shown).…”
mentioning
confidence: 99%